2021
DOI: 10.9734/arrb/2021/v36i830409
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Rice (Oryza sativa L.) Productivity and Farmer’s Income through the Implementation of Modified Double Rows Planting System

Abstract: Rice (Oryza sativa L.) productivity in Indonesia is leveling off. The study aims to determine the effect of the Jejer Manten double rows modified planting system on the growth, productivity, and economic feasibility of the rice farming system. The study was conducted in Lampung Province, Indonesia from 2016 to 2018. The study was arranged using a split-plot design with 3 replications. The treatment consisted of two factors namely: planting system (S1 = Jajar Tegel, S2 = Jajar Legowo double rows 2:1, and S3 = J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 14 publications
(12 reference statements)
4
10
0
Order By: Relevance
“…The planting density of Jejer Manten is 20% higher than a standard tile transplanting system, and it is 9.9% lower than Jajar Legowo type 2:1. Even though Jejer Manten has a lower plant population than Jajar Legowo, a previous study [12] found that the yield of Jejer Manten was 6% higher than Jajar Legowo type 2:1.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The planting density of Jejer Manten is 20% higher than a standard tile transplanting system, and it is 9.9% lower than Jajar Legowo type 2:1. Even though Jejer Manten has a lower plant population than Jajar Legowo, a previous study [12] found that the yield of Jejer Manten was 6% higher than Jajar Legowo type 2:1.…”
Section: Introductionmentioning
confidence: 84%
“…Some researchers explained Jajar Legowo and Jejer Manten could increase the yield compared to a standard tile transplanting system due to the border effect [10,12]. The border effect is the plant's response in its performance to the different conditions between the outermost rows and the inner rows.…”
Section: Introductionmentioning
confidence: 99%
“…The Jrw-B treatment produced a higher grain yield than the Tegel, Jrw-A, Jrw-B, Jrw-C, and Jrw-D treatments. The jajar legowo 2:1 planting system has a higher border effect than the square or jajar legowo 4:1 planting system (Asnawi et al, 2021). The plants' location influences the increase in photosynthesis at the edge of the row, where they receive relatively more maximum sunlight.…”
Section: Yield and Yield Componentsmentioning
confidence: 99%
“…The plants that should be planted in the empty rows are inserted into the rows (Abdulrachman et al, 2013). Increased side plants are the goal of the jajar legowo planting system (border effect) (Asnawi et al, 2021). The previous studies reported that the jajar legowo planting system affected rice growth (Sartika et al, 2021) and increased grain yield per hectare and rice yield components, including the panicles per hill, number of grains per panicle and 1000-grain weight (Liu et al, 2019;Susilastuti et al, 2018;Suweta et al, 2021).…”
Section: Abstrakmentioning
confidence: 99%
See 1 more Smart Citation